2016
DOI: 10.1111/cge.12720
|View full text |Cite
|
Sign up to set email alerts
|

A series of 38 novel germline and somatic mutations of NIPBL in Cornelia de Lange syndrome

Abstract: Cornelia de Lange syndrome is a multisystemic developmental disorder mainly related to de novo heterozygous NIPBL mutation. Recently, NIPBL somatic mosaicism has been highlighted through buccal cell DNA study in some patients with a negative molecular analysis on leukocyte DNA. Here, we present a series of 38 patients with a Cornelia de Lange syndrome related to a heterozygous NIPBL mutation identified by Sanger sequencing. The diagnosis was based on the following criteria: (i) intrauterine growth retardation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…No large rearrangements of the NIPBL were identified in the patients analyzed. The frequency of alterations detected in this study was lower compared to the previous reports (31,9% vs. 60–80%) (2, 1618). This low rate of detected alterations can be explained by selection bias since 15 previously NIPBL -negative patients were included in the study (10).…”
Section: Discussioncontrasting
confidence: 94%
“…No large rearrangements of the NIPBL were identified in the patients analyzed. The frequency of alterations detected in this study was lower compared to the previous reports (31,9% vs. 60–80%) (2, 1618). This low rate of detected alterations can be explained by selection bias since 15 previously NIPBL -negative patients were included in the study (10).…”
Section: Discussioncontrasting
confidence: 94%
“…In a questionnaire study, GERD was more common in individuals with NIPBL variants (71%) than in those with SMC1A variants (60%) 3 . In a small series of 38 individuals with NIPBL variants, 55% had GERD 91 , and in a series of 43 clinically diagnosed individuals, the disease was more common in those with classic phenotypes (known to be caused predominantly by NIPBL variants) 92 . In this study group, aged 6-32 years, 65% of participants demonstrated inflammation of the lining of the oesophagus (oesophagitis) at endoscopy.…”
Section: Organ System Manifestations Gastroenterologymentioning
confidence: 97%
“…It is caused by genetic alterations in NIPBL , SMC1A , SMC3 , HDAC8 , and RAD21 ( Krantz et al, 2004 ; Tonkin et al, 2004 ; Musio et al, 2006 ; Deardorff et al, 2007 , 2012a , b ). To date, genetic alterations in NIPBL have been detected in approximately 70% of CdLS patients (OMIM: 608667) ( Nizon et al, 2016 ). Genetic variants affecting gene splicing account for 15% of NIPBL mutations ( Mannini et al, 2013 ; Teresa-Rodrigo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%